ANALISIS BAHAN KIMIA OBAT ASAM MEFENAMAT DALAM JAMU PEREDA NYERI YANG BEREDAR DI NGAWI DAN ONLINE SHOP SECARA KLT DAN SPEKTROFOTOMETRI UV-VIS - Harjanti, Reslely; Pratiwi, Intan; Sarimanah, Jamilah (Jurnal Farmasi & Sains Indonesia, 2023)
One of the medicinal chemicals (BKO) that is abused in herbs preparations for pain reliever is mefenamic acid. Mefenamic acid is a class of non-steroidal anti-inflammatory drug (NSAID). The addition of mefenamic acid in herbs medicine aims to increase the effect of pain relief, but can caused harmful effects, including digestive tract disorders, hemolytic anemia, and seizures. The purpose of this study is to determine the presence of mefenamic acid in pain reliever herbs circulating in Ngawi and online shop.The samples in this study were several brands of pain reliever herbs from 4 herbal medicine shops (A,B,C, and D). This research is using purposive sampling method based on inclusion criteria. Samples was analyzed qualitatively by thin layer chromatography (TLC) method using cyclohexane:chloroform: methanol:glacial acetic acid (60:30:5:5) as mobile phase and silica GF254 as stationary phase. Quantitive analysis using spectrophotometry UV-Vis method. The results showed that 10 of 16 samples of herbal pain reliever were positive for mefenamic acid with levels ranging from 1.28% -7.30%. The UV-Vis spectrophotometric analysis method suitable for the analysis of mefenamic acid in herbal medicine for pain reliever based on validation results that meet the requirements includes linearity with r value 0.99956, accuracy 8 ppm was 100.32%, 10 ppm was 100.84%, 12 ppm was 100.61%, precision 1.33%, LOD 0.8914299023 ppm, and LOQ 2.701302734 ppm.